Optimization of Lipase Production from Local Bacteria Isolate with Palm Oil Inducer - Dwi May Indriyani; Nurhasanah Nurhasanah; Dian Herasari (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2021)
A lipase is a group of hydrolase enzymes with multi-functional abilities such as catalyzing hydrolysis, alcoholysis, esterification, interesterification, and synthesis of organic compounds. The purpose of this study was to obtain the optimum conditions for lipase production and to study the effect of adding a palm oil inducer on the production of lipase from local bacterial isolates. The method used in this study included the rejuvenation of local bacterial isolate cultures, optimization of production, which included pH, palm oil inducer, and incubation time. The lipase activity test was carried out by using the acid-base titration method with the phenolphthalein indicator. The results showed that the optimal conditions for lipase production occurred at pH 5 with an activity value of 7.5 U/mL and an incubation time of 18 hours with an activity value of 13.83 U/mL. The addition of a 10% (v/v) palm oil inducer increased the value of lipase activity to 8.75 U/mL.